A study on the personal digital archiving practices of student video game developers in the Philippines - Toda, Zachary P. (School of Library and Information Studies, University of the Philippines Diliman, 2018)
Video gaming has changed from a "geek" hobby, to a mainstream entertainment giant. In 1016 alone, the growth of the industry in the Philippines was valued at PHP 10.8 Billion. The majority of this growth was due to mobile and PC game development. However, video game preservation is limited to the colleges and universities that offer programs in video game development. While these are left with the university, it is common among students and alumni to have personal copies of their creations within their own storage drives. The availability of cheap digital storage has helped in the creation of Personal Digital Archives (PDAs). This study aims to study the Personal Digital Archiving practices of video game developers in the Philippines. To do this, the study will make comparisons between PDA and the OAIS framework. Six participants were selected through snowball sampling. Excerpts from the interviews were compiled to provide sufficient answers. The study revealed that the respondents primarily used personal computers or laptops, external storage media, and cloud storage services for their PDAs. Its complexity was dependent on the developers' education, work experience, and size of their development team. They serve as the producer and as the management for their personal archives. Factors had induced the creation of PDAs include future reference, personal history and achievement, identity, and fear of loss. The developers' familiarity of digital preservation practices reflected the integrity and freedom of access of PDAs.